(3GdTGajI aj GdJUQjas - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s
(3ChdgG (B:s
(3hHYO abO SCdfj ef dG jSYfj eNGdaJg hdG jdjb eNGdaJg Cf CdMb HebOeJj aj GdEYQGH ebOeI aj GdJUQja Ydi fMhgG hebOeI aj GdNW aCLHJg SGFdGGdJUQja Yde HCUhd JYQa Hg CMhGd HfjI Gdcde GdJj djSJ HEYQGHs
(3BNQgG (B:s
(3aEf Lgd aEf CedjJ aGdjGA fMh eJi hEdG aCda hEfeG cJHhG GdPj HGdjGA dbhdge dOjc hcdG jcJH Ydi GdhLgjf dGMJeGdg hCeG GdMQha ade jcJH efgG HGdjGA ZjQ Hdi hEdi hYdi hMJis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1020s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas